2011
DOI: 10.2147/ceg.s16168
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab therapy for moderately severe Crohn’s disease and ulcerative colitis: a retrospective comparison over 6 years

Abstract: Background:Infliximab has shown benefit in Crohn’s disease (CD) and ulcerative colitis (UC).Objective:Evaluation of long-term outcome of therapy for both diseases.Methods:We analyzed retrospectively patients treated at infusion centers from one institution. Demographic, laboratory parameters leading up to biologic therapy and the subsequent pattern of outcomes in either disease were established as a database. Initial failure, subsequent need to change therapy, or need to adjust therapy were evaluated. Kruskal–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Seow et al 33 reported that ATI development rates were significantly higher in UC patients in comparison with previous reports concerning CD patients, but in another study, no statistically significant difference in therapy outcome between the groups was found. 34 In our study, no difference was discernible as to either ATI formation or infliximab therapy failure in UC versus CD patients, although the number of UC patients was limited (n = 34) so the study may be underpowered to detect such difference.…”
Section: Discussioncontrasting
confidence: 53%
“…Seow et al 33 reported that ATI development rates were significantly higher in UC patients in comparison with previous reports concerning CD patients, but in another study, no statistically significant difference in therapy outcome between the groups was found. 34 In our study, no difference was discernible as to either ATI formation or infliximab therapy failure in UC versus CD patients, although the number of UC patients was limited (n = 34) so the study may be underpowered to detect such difference.…”
Section: Discussioncontrasting
confidence: 53%
“…Median follow-up in this group was 4.5 years; importantly, however, primary non-responders were excluded. A single-center retrospective study in Canada demonstrated a markedly lower surgical rate, with only 5/71 (7%) with a median follow-up of 62 months [36]. There have been several other studies with shorter follow-up whose rates of surgery in biologic-treated patients range from 15% to 33% [37, 38, 40].…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…(2013) [35]1993–2010Retrospective multi-center276*Infliximab18% no prior surgery for CD; 24% prior surgery for CD54 months (median)Alzafir et al . (2011) [36]2002–2008Retrospective single-center71Infliximab7%62 months (median)Caviglia et al . (2007) [37]1999–2005Retrospective single-center40Infliximab20%27 months (median)Ljung et al .…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…The concept of a COS, ''an agreed standardised set of outcomes that should be measured and reported as a minimum in all clinical studies and trials in specific areas of health or health care'', was pioneered in Rheumatology 8 and the success in overcoming recognised universal outcome research barriers, was instrumental in the inception of the Core Outcome Measures in Effectiveness Trials (COMET) initiative subsequently adopted by other specialities. The COMET database currently holds nine registered IBD projects: six systematic reviews to inform the development of COS focusing on efficacy and safety in clinical trials in paediatric IBD, 9 IBD, 10 UC, 11 pouchitis, 12 fistulising perianal CD, 13 and CD 14 , and three COS development studies for fistulising perianal CD, 15 patient-centred outcomes in IBD, 16 and paediatric IBD. 17 There is no registered COS for RWE in IBD.…”
Section: Introductionmentioning
confidence: 99%